Empire of the Qing in 1912-1924: Microstate or Quasi-state? - A. G. Nesterov; C. Rao (Научный диалог, 2017)
The status of the dynasty and Empire of the Qing in China after the Xinhai revolution is discussed. It is reported that in accordance with the terms of the Emperor Pu Yi’s refusal of the throne of China, he retained the Imperial title and the historic centre of Beijing - Forbidden city - as a possession. It is noted that the Republic of China recognized the Emperor Qing as the “foreign monarch.” The article shows that the document “Preferential terms” containing information about the special conditions provided by the Chinese Republic to the Emperor Qing, is in much the same with “Guarantee Act” - a document issued by the Italian government in March 1871 after the army of the Kingdom of Italy in September 1870 occupied Rome and was eliminated the temporal power of the Pope. It is proved that in many respects the Qing Empire in 1912 acquired the actual status of the microstate, when in fact this status is not sought. The authors argue that the Qing Empire in the years of 1912-1924 actually remained a quasi-state and did not realise a political possibility of transformation in the microstate. The reason is the unwillingness of the leaders of the Qing monarchy to abandon the idea of the restoration of the monarchy in China and to create miniature state. It is concluded that for these reasons the final destruction of the Qing Empire in 1924 was the natural result of its existence.